The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1108/jeas-04-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of stock market volatility: evidence from Dubai financial market

Abstract: Purpose The purpose of this paper is to assess the sources of Dubai Financial Market Index volatility shocks if they are from its own or previous shocks on the one hand, or if they are out board shocks (FSTE and S&P500) on the other. Design/methodology/approach A daily time series data were collected over the period 1st January 2014-31st December 2015 and the generalized autoregressive conditional heteroskedasticity (GARCH) methodology was implemented. Findings Empirically, the authors find that the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Salameh and Alzubi (2018) investigated Dubai stock market for volatility spillover with the UK and the USA from January 2014 to December 2015 using ARCH and GARCH models. The analysis revealed that Dubai Financial Market Index was affected by its own disturbances and from S&P500 but not from FTSE.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Salameh and Alzubi (2018) investigated Dubai stock market for volatility spillover with the UK and the USA from January 2014 to December 2015 using ARCH and GARCH models. The analysis revealed that Dubai Financial Market Index was affected by its own disturbances and from S&P500 but not from FTSE.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The outcomes also showed that the unpredictability of FSTE do not underwrite to the volatility of DFM, while S&P-500 pay to the volatility of DFM which means that outside shocks can influence the volatility of DFM. In addition, APX affects Dubai Financial Market Index (DFM) [10].…”
Section: Review Of Literaturementioning
confidence: 99%
“…As a result, UAE investors seek capital on outside their home country as their UK investment options increase. Improving the transparency of transactions through information technology will increase the efficiency of Dubai's financial markets [5]. Different methods are used in each margin trading policy stage to estimate the impact of policies on China's stock market volatility, including but not limited to VAR models, impulse response functions and ARCH regression models [6].…”
Section: Introductionmentioning
confidence: 99%